PERLINDUNGAN HUKUM DALAM MENJAMIN KEAMANAN DAN KESEJAHTERAAN KURIR DI TENGAH RISIKO TINDAKAN MERUGIKAN KONSUMEN - Liza Hani Saroya Wardi; Muhammad Fadjri (Journal of Innovation Research and Knowledge, 2026)
This paper aims to describe how women’s space “comes into being” through the nensek tradition in Keloke Hamlet, Batujai Village, Praya Barat District, Central Lombok, by employing Heidegger’s philosophical approach. The research was conducted through field observations and in-depth interviews with women practitioners of nensek as the primary methods of data collection. The data were then analyzed inductively and iteratively using a case study approach. The analysis began with a comprehensive review, followed by data reduction through thematic categorization based on Heidegger’s concepts: (1) Dasein as the creator of space, (2) dwelling authentically within space, and (3) identity as Dasein in space. Findings from everyday experiences reveal that nensek is the main reason for the existence of women’s space in Keloke. The nensek tradition is not merely a craft, but a mode of being-in-the-world that provides identity and spiritual meaning for Sasak women in Keloke. The spatial dimension of nensek shows that it generates an economic space to meet daily needs, while at the same time offering a spiritual and expressive space where Sasak women reconnect with their ancestors as evidence of fulfilling their cultural mandate and role as heirs of tradition. Through the practice of nensek, Sasak women in Keloke are able to demonstrate their existence authentically—encountering themselves, their ancestors, and a deeper world—thereby transcending the conditions of their everyday lives.